Some heavy metals in the muscle of Capoeta trutta: risk assessment for the consumers - Eroglu, M.; Dusukcan, M.; Canpolat, O. (C M B Assoc, 2016)
This study was carried out to detect the concentrations of some heavy metals (copper, iron, zinc, cadmium and chromium) in the muscle of Capoeta trutta (Heckel, 1843) and in their surrounding water in order to study the potential human risk of consumption. The relationship between the heavy metal load of fish and some of their biological aspects (weight, length and sex) was also examined. In addition, the accumulation factors of heavy metals in this species were determined. The concentrations of Cu, Fe, Zn, Cd and Cr in water and muscle samples were analysed using ICP. Cu, Zn and Fe were detected in all samples, but Cd and Cr were not found in detectable levels. The results showed that heavy metals accumulation in muscle of fish was higher than that in the water. It was found that the level of heavy metals in the muscle of fish showed differences according to weight, length and sex of fish.
Keywords: Heavy metal accumulation; accumulation factor; muscle; Capoeta trutta